How grassroots women-led networks are strengthening resilience and reducing climate-conflict risks: Experience from Latin America and the Caribbean - Palou Zuniga, Nohelia; Madurga Lopez, Ignacio (2025)
Across Latin America and the Caribbean (LAC), women are uniquely positioned to address the dual crises of climate change and conflict. Their community networks, rooted in caregiving, mutual aid, and local knowledge, play a critical and often underrecognized role in strengthening social cohesion, protecting natural resources, and responding to environmental shocks.